IMMEDIATE EFFECT OF MENTAL SIMULATION ON SELF-CONFIDENCE AND PERFORMANCE WHEN PERFORMING STANDING SALTO BACKWARDS IN GYMNASTS - Sarra Hammoudi Nassib; Dhouha Cherni; Sabra Hammoudi Riahi; Sameh Menzli Wali; Bessem Mkaouer (University of Ljubljana Press (Založba Univerze v Ljubljani), 2022)
The aim of this study was to examine the combined effect of mental imagery as well as visualization on performance, self-confidence, and self-report during the performance of the standing salto backward. Eighteen gymnasts (age 22.11 ± 1.71 years) voluntarily participated in this study. Once the warm-up was completed, subjects performed a standing salto backward tucked on the force-plate to determine the baseline performance before each experimental session. Subsequently, subjects were given specific intervention instructions and were asked to perform the standing salto backward tucked to the best of their ability. Participants were asked to engage in two mental strategies namely mental imagery and visualization for 1 min just before performing (Standing salto backward tucked). The results of the present study show that the combined mental simulation (MI and V), generate a potential improvement in performance during the execution of the standing salto backward as well as self-confidence and self-evaluation.